The Effect of Eurycoma longifolia Jack on sICAM-1 and eNOS in Rats with High Fat Diet - Anas Omar Ashkurfu; Kis Djamiatun (Faculty of Medicine, Diponegoro University, 2018)
Background: High fat diets are known to cause a positive fat balance and consequently to the accumulation of adipose mass, this diet does not seem to stimulate fat oxidation in the same way in obese and lean subjects. HFD was an inducing factor for ICAM-1 expression in the aorta of Wistar rats. HFD effect on ICAM-1 seems to be time dependent. ICAM-1 is one of the first events in the formation of atherosclerotic lesions. HFD up-regulated Cav-1, regulated expression other biomarker in HFD is eNOS. Recent studies showed that E. longifolia Jack protected HFD animal model from atherosclerosis based on the reduce atherosclerotic plaque size and formation HFD-rats treated with E. longifolia Jack.Objective: To prove that Eurycoma longifolia has anti inflammatory effect on endothelial cell blood vessels of Sprague Dawley rat with high fat diet.Method: Study design was experimental study, by used Randomized Post Test only Control Group Design with Kruskal-Wallis test was used to analyze the differences among groups and followed by a Mann Whitney test. Treatment is ethanolic or water extract of Eurycoma longifolia Jack, and out come are sICAM-1 and eNOS levels. Thirty Sprague Dawley (SD) Rat, were divided into 6 groups. C(-) was SD group, C(+) was group with HFD, X1 (SD treated with EL dosage 10 mg/kg), X2 (SD treated with EL dosage 15 mg/kg), X3 (HFD treated with EL dosage 10 mg/kg), X4 (HFD treated with EL dosage 15 mg/kg).